STUDI EKSPERIMEN KEKUATAN MEKANIK DAUN NANAS HUTAN DENGAN METODE PENGUJIAN TARIK - Firman, Firman; Hasbi, Muhammad; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2018)
The purpose of this research is to know the strength of pineapple forest leaf fiber with NaOH treatment.Thisresearch material used of forest pineapple fiber. The treatment of the specimen was carried by immersionwith 5% NaOH solution, sun and air, respectively for 2 hours. The specimen test was made based on ASTMD 3379-75 standard for tensile test specimens.NaOH tretment effect on tensile strength of peneaple forestleaf fiber. The test result showed that the highest tensile test value was found on the specimen with NaOHtreatment of 78.17403 N/mm2. Whose tensile strength tends inncrease after experiencing alkali treatment(NaOH). Tretment of air and sun less influence of tensile strength of peneapple leaf fiber. Then value oftensile test of sunlight pineapple forest 71.20283 N/mm2 and the value of tensile test of pineapple leaves forair treatment forest of 43.84033 N/mm2.Keywords : Forest pineapple leaf fiber, NaOH and tensile strength.